2010
DOI: 10.1088/0004-637x/711/2/990
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Alfvén and Kink Oscillations in Coronal Loops

Abstract: Observations have revealed ubiquitous transverse velocity perturbation waves propagating in the solar corona. However, there is ongoing discussion regarding their interpretation as kink or Alfvén waves. To investigate the nature of transverse waves propagating in the solar corona and their potential for use as a coronal diagnostic in MHD seismology, we perform three-dimensional numerical simulations of footpoint-driven transverse waves propagating in a low β plasma. We consider the cases of both a uniform medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
165
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(178 citation statements)
references
References 34 publications
(56 reference statements)
13
165
0
Order By: Relevance
“…Hence the oscillation amplitude is described by a kind of Gaussian profile for small time and by the exponential function for larger time. This result is similar to one found by Pascoe et al (2010Pascoe et al ( , 2011Pascoe et al ( , 2012 for propagating waves. The dashed line in (30) we obtain t dc /Π = 4(π 2 κ) −1 .…”
Section: Examination Of Figs 1-3 Reveals That the Solution Can Be Wrsupporting
confidence: 91%
See 1 more Smart Citation
“…Hence the oscillation amplitude is described by a kind of Gaussian profile for small time and by the exponential function for larger time. This result is similar to one found by Pascoe et al (2010Pascoe et al ( , 2011Pascoe et al ( , 2012 for propagating waves. The dashed line in (30) we obtain t dc /Π = 4(π 2 κ) −1 .…”
Section: Examination Of Figs 1-3 Reveals That the Solution Can Be Wrsupporting
confidence: 91%
“…In particular, it was shown with the use of connection formulae that in the linear approximation the waves damp exponentially with the distance from the driver, and the damping length has been calculated. The same problem has been studied numerically by Pascoe et al (2010Pascoe et al ( , 2011Pascoe et al ( , 2012. In particular, Pascoe et al (2012) have shown that the wave amplitude does not decay exponentially everywhere.…”
Section: Introductionmentioning
confidence: 95%
“…These azimuthal motions keep propagating along magnetic field lines (see the numerical simulations by, e.g., Pascoe et al 2010Pascoe et al , 2011. A detailed investigation of the energy transfer in the case of standing waves was done in Arregui et al (2011) by analyzing the Poynting flux in a two-dimensional configuration.…”
Section: Chromospheric Kink Wavesmentioning
confidence: 99%
“…In magnetic waveguides resonant absorption transfers wave energy from transverse kink motions to azimuthal motions localized in the inhomogeneous part of the waveguide. This process has been studied numerically by Pascoe et al (2010Pascoe et al ( , 2011 in the case of driven kink waves in coronal waveguides.…”
Section: Introductionmentioning
confidence: 99%
“…They are strongly damped in loop structures (Tomczyk & McIntosh 2009) which is also accounted for by mode coupling (e.g. Pascoe et al 2010;Terradas et al 2010). The propagating kink waves are observed to have a broadband power spectrum.…”
Section: Discussionmentioning
confidence: 99%